Ultra-wideband amplification composite bismuth-doped optical fiber with gradually changing transition core layer and preparation method and application thereof

CN122901997APending Publication Date: 2026-10-13SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611033152.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0008]为解决现有掺铋光纤因折射率与掺杂浓度阶跃突变所导致的光场能量集中于纤芯中心、外层铋活性中心利用不充分、增益谱波段衔接处凹陷明显以及增益带宽受限等问题,本发明提出一种具有渐变过渡纤芯层的超宽带复合掺铋光纤

Benefits of technology

1.本发明采用内层纤芯折射率高于外层纤芯折射率的纤芯结构,结合折射率连续渐变分布的过渡层,实现1310 nm波段基模光场的受控向外扩展,在不牺牲波导约束性能的前提下,基模光场与外层硅相关铋活性区的重叠因子较常规阶跃方案提升,显著提高E+S波段的增益。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122901997A_ABST
    Figure CN122901997A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of ultra-wideband composite bismuth-doped optical fiber with gradual transition core layer, and the refractive index of fiber core is designed with layer 2 gradual transition layer, so that the doping concentration is doubly continuous and gradually distributed.The optical fiber is sequentially layer 1 inner core, layer 2 gradual transition layer, layer 3 outer core and low refractive index fluorine-doped silica cladding, pure silica cladding and organic protective layer from inside to outside.The present application can widen the gain bandwidth of bismuth-doped optical fiber to O+E+S band.In a preferred embodiment, the ultra-wideband composite bismuth-doped optical fiber with gradual transition core layer is used in ultra-wideband fiber amplifier system, and the 20 dB gain bandwidth can reach 183 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optical fiber communication and optical fiber amplifier technology, specifically relating to an ultra-wideband amplification composite bismuth-doped optical fiber with a gradient transition core layer, its preparation method and application. Background Technology

[0002] With the rapid development of artificial intelligence, cloud computing, and data center communication technologies, data volume is exploding, and traditional C-band (1530–1565 nm) amplifiers can no longer meet future transmission demands. Developing fiber optic amplifiers beyond the C-band, especially those capable of achieving ultra-wideband amplification in the O+E+S bands (1260–1530 nm) using a single fiber, has become a major industry objective. Bismuth-doped fibers can simultaneously contain two types of luminescent centers: phosphorus-associated bismuth active centers (BAC-P) and silicon-associated bismuth active centers (BAC-Si). The coverage bands of these two luminescent centers are perfectly aligned, providing complete coverage of the O+E+S bands.

[0003] To achieve synergistic effects between BAC-P and BAC-Si light-emitting centers, existing solutions include different combinations of bismuth-doped fibers, modulation of pump wavelength, and layered doping. Among these, the Firstov team from the Russian Academy of Sciences, in collaboration with Huazhong University of Science and Technology, employed a layered doping scheme, achieving broadband amplification in the 1260–1420 nm range (DOI: 10.1364 / OL.567880) and 1310–1470 nm range (DOI: 10.1117 / 12.3076456), respectively, with bandwidths of approximately 160 nm. However, this still falls short of the industry goal of fully covering the O+E+S bands.

[0004] Its core bottleneck lies in the fact that the refractive index and doping concentration of the fiber core are both abruptly abruptly changed, the optical energy is concentrated in the center of the fiber core, and the overlap with the outer doped region is low, resulting in insufficient utilization of different bismuth active centers and uneven gain in different bands. In particular, the gain dip is obvious at the junction of adjacent bands, and a smooth broadband gain spectrum cannot be formed.

[0005] To address the energy concentration issue in the optical field caused by step structures, patent CN115933048B employs a graded refractive index design in erbium-doped fiber (EDBF) to reduce intermodal crosstalk in BDBF amplifiers. This achieves optimal overlap between the signal and pump light fields, resulting in balanced gain for different signal modes. However, this approach only involves changes in the refractive index profile; the doping concentration remains a step-like abrupt change, and the optimization of gain bandwidth is not considered.

[0006] A few other technologies attempt to use a gradual doping concentration scheme, such as patent CN115032735B, which adjusts the doping concentration by alternating uniform deposition to reduce the noise figure in the C+ band and improve gain. However, its refractive index structure is still step-type, and it does not eliminate the refractive index abrupt change and optical leakage caused by the abrupt interface. Patent CN113359229A designs a large core diameter rare earth fiber with a gradual concentration (the core refractive index is distributed in a trapezoidal or triangular shape), which improves the beam quality of the output laser, but does not involve the expansion of gain bandwidth.

[0007] In summary, existing technologies mainly focus on optimizing refractive index distribution or changing doping concentration to improve fiber performance, but have not yet achieved a dual continuous gradient of refractive index and doping concentration in the same fiber to match the requirements of synergistic excitation of multiple bismuth active centers. Fundamental problems such as optical field energy concentration, insufficient utilization of active centers, and gain dips at band junctions caused by the step refractive index and doping concentration interface remain unresolved, severely restricting the full expansion of bismuth-doped fiber gain bandwidth and the realization of ultra-wideband flat amplification in the O+E+S bands. Summary of the Invention

[0008] To address the problems of concentrated optical energy at the core center, insufficient utilization of outer bismuth active centers, significant dips at the gain spectrum band transition, and limited gain bandwidth in existing bismuth-doped fibers due to abrupt changes in refractive index and doping concentration, this invention proposes an ultra-wideband composite bismuth-doped fiber with a graded transition core layer. The fiber core has a coaxial three-layer structure, consisting of: layer 1 (inner core) made of bismuth-phosphorus co-doped silica glass; layer 2 (graded transition layer) made of bismuth-phosphorus-germanium co-doped silica glass; and layer 3 (outer core) made of bismuth-germanium co-doped silica glass. In layer 2, the refractive index distribution and the concentrations of both types of bismuth active centers are continuously and gradually varied, allowing the doped regions of BAC-P and BAC-Si to naturally connect radially. The fiber can achieve ultra-wideband amplification with a gain bandwidth of not less than 166 nm in the O+E+S bands.

[0009] To achieve the above technical objectives, this application adopts the following technical solution.

[0010] This invention proposes an ultrawideband composite bismuth-doped optical fiber with a graded-transition core layer. The optical fiber comprises, from the inside out, a core, a low-refractive-index fluorine-doped silica cladding, a pure silica cladding, and an organic protective layer. The cladding diameter is 125 μm, the core diameter is 6.4–8.4 μm, the pure silica cladding is SiO2 glass, and the organic protective layer is polyimide or UV-cured acrylate.

[0011] The fiber core adopts a coaxial multilayer structure, consisting of an inner core layer (layer 1), a gradient transition layer (layer 2), and an outer core layer (layer 3) from the inside out, with each layer using quartz glass as the substrate. Layer 1 is a bismuth-phosphorus co-doped quartz glass, primarily forming BAC-P covering the O+E band; layer 3 is a bismuth-germanium co-doped quartz glass, primarily forming BAC-Si covering the E+S band. Layer 2 is a bismuth-phosphorus-germanium co-doped quartz glass with a radial thickness d = r2 - r1, ranging from 0.8 to 1.2 μm. Its refractive index exhibits a continuous gradient from high inside to low outside along the radial direction, eliminating the step refractive index interface of existing double-layer fiber cores.

[0012] The concentrations of BAC-P and BAC-Si in this layer exhibit a continuous, gradual distribution along the radial direction. The cross-sectional area ratios of layers 1, 2, and 3 are 22%–41%, 28%–55%, and 15%–50%, respectively, and their sum is 100%. Given a core radius r3, ranging from 3.2 to 4.2 μm, the radii r1 and r2 of each layer can be uniquely determined by combining the aforementioned cross-sectional area ratios. Preferably, the cross-sectional area ratio of the inner core layer of layer 1 is 25%–41%, the cross-sectional area ratio of the gradient transition layer of layer 2 is 38%–55%, and the cross-sectional area ratio of the outer core layer of layer 3 is 15%–34%. This ratio achieves an optimal balance between gain bandwidth and gain flatness. By adjusting the ratio of the cross-sectional area ratios of the three layers, optimal control can be achieved among O+E band gain, E+S band gain, and waveguide confinement capability.

[0013] The present invention further defines the structure of the optical fiber through the following parameter model: The refractive index distribution characteristics of the optical fiber are as follows: the refractive index in the region [0, r1] of layer 1 is a constant value n1, and the refractive index in the region [r2, r3] of layer 3 is a constant value n2, satisfying 1.452 > n1 > n2 > 1.444 (relative to the refractive index n of pure quartz cladding). SiO2 =1.444). The refractive index of the graded transition layer 2 within the radial interval [r1, r2] follows the following graded model: In the formula, r1 and r2 are the inner and outer radii of the gradient transition layer 2. k The refractive index distribution shape factor has a value range of 1. k ∈[1.5,2.8].

[0014] Preferably, k is 1.8~2.5, which results in a smooth transition of the optical field and waveguide confinement capability. This can effectively guide the optical field to expand outward, increase the overlap factor between the fundamental mode optical field and the outer BAC-Si, and avoid mode distortion caused by excessive refractive index difference.

[0015] The concentration distribution characteristics of the active centers in the optical fiber are as follows: the BAC-P concentration and BAC-Si concentration within the radial interval [r1, r2] of the graded transition layer 2 follow the following graded model. , in, m It is the gradient exponent, and its value range is 1≤ m ≤3, the preferred value is m=2; C 1 represents the BAC-P concentration at radial position r1 of layer 1. C 3 represents the BAC-Si concentration at radial position r2 of layer 3; and is defined as follows: C 1≥3×10 16 cm 3 , C 3≥9×10 16 cm 3 .

[0016] Preferably, in layer 1 C 1 is (3~5)×10 16 cm 3 In layer 3 C 3 is (9~12)×10 16 cm 3 The lower limit of this concentration was determined through controlled variable simulation. When the BAC-P concentration is below 3 × 10⁻⁶... 16 cm 3 At that time, the gain coefficient of the O+E band is insufficient, and it cannot smoothly connect with the gain of the E+S band; when the BAC-Si concentration is lower than 9×10 16 cm 3 At these concentrations, the S-band gain drops significantly, making it impossible to achieve ultra-wideband flat amplification in the O+E+S bands. The aforementioned concentration range ensures that the two types of bismuth active centers work synergistically to provide stable and effective gain for the optical fiber. Detailed simulation results are shown in Figure 4 and the parameter analysis in the examples section.

[0017] By designing a concentration-gradient and refractive index-gradient transition layer, the peak wavelengths of the emission spectra of BAC-P and BAC-Si were effectively adjusted, making the emission intensity equal in different bands and the emission spectra smoothly connected. This eliminated the gain spectrum dip caused by traditional step doping and improved the gain connection between the O+E and E+S bands.

[0018] The refractive index of the optical fiber is related to the elemental doping concentration as follows: the change in refractive index and the phosphorus and germanium doping concentrations satisfy the following linear correlation model. Where, β P The value represents the change in refractive index caused by a unit molar percentage of P₂O₅, ranging from (8.5 to 9.0) × 10⁻⁶. 4 mol% 1 ;β Ge The value represents the change in refractive index caused by a unit molar percentage of GeO2, ranging from (1.3 to 1.4) × 10⁻⁶. 3 mol% 1 .

[0019] The calculation in this invention uses the typical value β. P =9.0×10 4 mol% 1 β Ge =1.4×10 3 mol% 1 Because the bismuth doping concentration is low (on the order of hundreds of ppm), this model assumes that the contribution of bismuth doping to the refractive index of the quartz matrix is ​​negligible, affecting only the concentration of active centers. During the calculation, the concentrations of phosphorus and germanium doping are first calculated from the target refractive index difference, and then the gradient variation range of each component is allocated in combination with the active center concentration model to ensure that both the refractive index and the concentration of bismuth active centers change continuously and gradually, thus solving the problem of discontinuous connection of gain bands.

[0020] The present invention also provides an ultra-wideband fiber amplification system, characterized in that the system comprises the above-mentioned ultra-wideband composite bismuth-doped fiber with a gradient transition core layer.

[0021] This invention also provides a method for preparing an ultra-wideband composite bismuth-doped optical fiber with a gradient transition core layer, comprising the following steps: preparing the optical fiber according to any one of claims 1 to 13 using an improved chemical vapor deposition method combined with solution doping; adjusting the flow ratio of GeCl4 and POCl3 during the deposition process to make the refractive index of the gradient transition layer 2 continuously and gradually change along the radial direction as a power function; and controlling the soaking time and solution concentration of the solution doping to make the BAC-P concentration and BAC-Si concentration in the gradient transition layer 2 continuously and monotonically decreasing and continuously and monotonically increasing along the radial direction, respectively.

[0022] Furthermore, the method also includes the following steps: A porous preform layer consisting of the outer core of layer 3, the gradient transition layer of layer 2, and the inner core of layer 1 is sequentially deposited inside a quartz liner. The deposited porous preform is then immersed in a bismuth-containing doping solution for solution doping. The preform is formed through dehydration, sintering, and vitrification processes. The preform is then shrunk, stretched, deposited with an outer cladding layer, and drawn a second time to obtain the optical fiber.

[0023] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention employs a fiber core structure with an inner core refractive index higher than that of the outer core, combined with a transition layer with a continuously gradually varying refractive index, to achieve controlled outward expansion of the fundamental mode optical field in the 1310 nm band. Without sacrificing waveguide confinement performance, the overlap factor between the fundamental mode optical field and the outer silicon-related bismuth active region is improved compared to the conventional step scheme, significantly increasing the gain in the E+S band.

[0024] 2. This invention achieves seamless connection between the BAC-P and BAC-Si doped regions by continuously and gradually distributing the concentration of bismuth active centers within the gradient transition layer, eliminating the gain dip in the O-band and E-band connection region in the traditional step doping scheme, and realizing ultra-wideband flat gain in the O+E+S band.

[0025] 3. By adjusting parameters such as the cross-sectional area ratio of the three fiber cores, the thickness of the gradient transition layer, and the refractive index distribution shape factor, this invention can flexibly control the gain start wavelength, cutoff wavelength, and gain bandwidth of the optical fiber to meet the needs of different application scenarios. It has significant application value in O+E+S band ultra-wideband optical fiber communication systems.

[0026] It should be understood that, within the scope of this invention, the above-described technical features of this invention and the technical features specifically described below (such as in the embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the radial cross-sectional structure of the ultrawideband composite bismuth-doped optical fiber with a graded transition core layer according to the present invention. Figure 2 This is the radial distribution curve of doping concentration and refractive index of the ultra-wideband composite bismuth-doped optical fiber with a gradient transition core layer of the present invention. Figure 3 This is a schematic diagram comparing the gain spectra of the optimal structural scheme embodiments 5 and 6 of the present invention with those of an existing double-layer structure (comparative example). Figure 4 This is a schematic diagram comparing the gain spectra of the optical fiber of the present invention under different bismuth active center concentration ratios; wherein Figure 4 (a) Gain spectrum curves with fixed BAC-Si concentration and varying BAC-P concentration. Figure 4 (b) shows the gain spectrum curves with fixed BAC-P concentration and varying BAC-Si concentration. The values ​​in parentheses in the figure represent the 20 dB gain bandwidth of the corresponding structure. Detailed Implementation

[0028] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0029] In each embodiment, the parameters such as refractive index, concentration, and thickness are typical values ​​and preferred ranges based on simulation verification. Performance tests for all embodiments used 1240 nm bidirectional pumping with a total pump power of 700 mW and a signal light input power of -30 dBm. Each embodiment varied the spatial distribution weight of the active centers and the refractive index gradient morphology by selecting different proportions of the three-layer fiber core cross-sectional area, transition layer thickness, refractive index shape factor k, doping concentrations C1 and C3, and concentration gradient index m.

[0030] To clarify the quantitative correlation between the concentration of bismuth active sites and gain, and to verify the lower limit of concentration, this invention conducts simulation analysis by controlling a single concentration change. The results are as follows: Figure 4 As shown. Figure 4 (a) The BAC-Si concentration was fixed at the optimal value of 9 × 10⁻⁶. 16 cm -3 When the BAC-P concentration increases from 1×10 16 cm -3 Increased to 3×10 16 cm -3 At that time, the 20 dB gain bandwidth was broadened from 120 nm to 175 nm; it was further increased to 6 × 10 16 cm -3 9×10 16 cm -3 At that time, due to the redshift effect and pump competition, the bandwidth narrowed to 149 nm and 123 nm, respectively. Therefore, the lower limit of BAC-P concentration should be 3 × 10⁻⁶. 16 cm -3 Below this value, the O+E band gain is insufficient, and the 20 dB gain bandwidth is less than 130 nm. Similarly, Figure 4 (b) The BAC-P concentration was fixed at the optimal value of 3 × 10⁻⁶. 16 cm -3 When the BAC-Si concentration is below 9×10 16 cm -3 The S-band gain is insufficient, and the bandwidth continues to narrow; therefore, its lower limit is set at 9×10.16 cm -3 .

[0031] Regarding the interaction mechanism of BAC-P and BAC-Si coexisting, they are independent bismuth active centers in the quartz matrix. The coexisting system mainly has two types of limiting effects: First, the pump competition effect, where 1240 nm pump light can be absorbed by both types of centers, and the population inversion efficiency will be reduced when the total bismuth concentration is too high; Second, the gain spectrum redshift effect caused by the increase in concentration. When the concentration of BAC-P and BAC-Si exceeds the threshold, the distance between active centers decreases, the distortion of the local coordination field is enhanced, the emission peak position shifts to the long wavelength direction as a whole, the stimulated emission cross section of the short wavelength (O band) decreases, the gain contribution weakens, resulting in the loss of short-wavelength gain and narrowing of bandwidth.

[0032] The gradient transition layer of this invention can spatially separate the concentration peaks of two types of active centers, avoiding the redshift and competitive absorption problems caused by excessively high local concentrations in step structures, while ensuring sufficient gain in each band; preferably, the concentration ratio is within the synergistic gain range, ensuring smooth band transitions and avoiding the negative effects of high concentrations. Figure 4 The simulation results shown are consistent.

[0033] The fiber optic design and performance simulation process in the following embodiments includes the following steps: First, parametric modeling is performed, with inputs of different cross-sectional area ratios of the three-layer fiber core, transition layer thickness, refractive index shape factor k, doping concentrations C1 and C3, and concentration gradient index m. The radius of each fiber core is calculated through geometric relationships, and the radial refractive index distribution, doping concentration distribution, and spatial proportion of each active center are output. Subsequently, the finite element method or finite difference beam propagation method was used to solve the fundamental mode optical field distribution in the range of 1260~1520 nm, calculate the overlap factor and effective mode field area of ​​each layer, and perform linear interpolation with a step size of 1 nm to obtain the full wavelength mode field parameters. Next, the absorption cross section, emission cross section, and upper level lifetime of BAC-P and BAC-Si as a function of wavelength are calculated. The steady-state rate equation is solved in combination with the mode field parameters to obtain the upper level particle number density distribution in the radial direction of the fiber. A set of power transfer equations was established, including forward / reverse pump light, forward signal light, and forward / reverse amplified spontaneous emission light. An iterative method was used to solve the equations, with a convergence threshold set to ≤10. -6 Finally, the wavelength-gain curve was calculated.

[0034] Example 1 This embodiment provides an ultrawideband bismuth-doped optical fiber with a graded transition core layer, which, from the inside out, comprises an inner core layer (layer 1), a graded transition layer (layer 2), an outer core layer (layer 3), a low-refractive-index fluorine-doped quartz cladding, a pure quartz cladding, and an organic protective layer. The inner core layer (layer 1) is bismuth-phosphorus co-doped quartz glass containing phosphorus-associated bismuth active centers (BAC-P); the outer core layer (layer 3) is bismuth-germanium co-doped quartz glass containing silicon-associated bismuth active centers (BAC-Si); the graded transition layer (layer 2) is bismuth-phosphorus-germanium co-doped quartz glass containing both BAC-P and BAC-Si. In this layer, the concentration of BAC-P decreases continuously and monotonically from the inside out radially, while the concentration of BAC-Si increases continuously and monotonically from the inside out radially, and the refractive index of this layer decreases continuously from the inside out radially.

[0035] In this embodiment, the total core radius is 4.2 μm, the core radius of the inner layer of layer 1 is 1.97 μm, the thickness of the gradient transition layer of layer 2 is 1.0 μm, and the outer core radius of the outer layer of layer 3 is 4.2 μm. The concentrations of BAC-P and BAC-Si within the gradient transition layer of layer 2 are continuously and gradually distributed according to a gradient exponent m=2, and the BAC-P concentration C1 at the radial position r1 is 5×10¹. 6 cm - ³, BAC-Si concentration C3 at radial position r2 = 12 × 10¹ 6 cm - ³; The refractive index distribution of the 2nd gradient transition layer decreases according to a power function, with a shape factor k=2. The refractive index difference between the inner radius (n1) and the outer radius (n2) is Δn1=0.008 and Δn2=0.006 (relative to pure quartz cladding). The cross-sectional area ratios of the inner core of layer 1, the 2nd gradient transition layer, and the 3rd outer core are 22%:28%:50%, and the sum of the three is 100%.

[0036] This fiber has a 20 dB gain bandwidth of 175 nm, covering a wavelength range of approximately 1300–1475 nm. The design employs a large core radius structure, significantly increasing the effective mode area and exhibiting good mode stability, making it suitable for high-power fiber amplification systems with large mode areas.

[0037] Example 2 This embodiment provides an ultrawideband bismuth-doped optical fiber with a gradient transition core layer, whose layered structure and doping active center type are the same as in Embodiment 1.

[0038] In this embodiment, the total core radius is 3.2 μm, the core radius of the inner layer of layer 1 is 1.95 μm, and the thickness of the gradient transition layer 2 is 1.0 μm. The refractive index distribution shape factor of the gradient transition layer 2 is k=2, and the refractive index difference between the refractive index n1 at the inner radius and the refractive index n2 at the outer radius is Δn1=0.008 and Δn2=0.006 (relative to pure quartz cladding). The concentration gradient index m=3, and the BAC-P concentration C1=3×10 16 cm - ³, BAC-Si concentration C3 = 9 × 10 16 cm - ³. The cross-sectional area ratios of the inner fiber core of layer 1, the gradient transition layer of layer 2, and the outer fiber core of layer 3 are 37%:48%:15%, and the sum of the three is 100%.

[0039] This optical fiber has a 20 dB gain bandwidth of 176 nm, covering a wavelength range of approximately 1300~1476 nm. It exhibits uniform gain distribution without significant dips, achieving a comprehensive balance between bandwidth, noise figure, and mode field constraints. It can serve as a benchmark for overall solutions and is suitable for general-purpose ultra-wideband fiber amplifiers.

[0040] Example 3 This embodiment provides an ultrawideband bismuth-doped optical fiber with a gradient transition core layer, whose layered structure and doping active center type are the same as in Embodiment 1.

[0041] In this embodiment, the total core radius is 3.2 μm, the core radius of the inner layer of layer 1 is 2.05 μm, and the thickness of the gradient transition layer 2 is 0.8 μm. The shape factor k of the refractive index distribution in the gradient transition layer 2 is 1.5, and the refractive index difference Δn1 = 0.008 and Δn2 = 0.006 (relative to pure quartz cladding) between the refractive index n1 at the inner radius and the refractive index n2 at the outer radius. The concentration gradient index m = 2, and the BAC-P concentration C1 = 3 × 10⁻⁶. 16 cm - ³, BAC-Si concentration C3 = 10 × 10 16 cm - ³. The cross-sectional area ratios of the inner fiber core of layer 1, the gradient transition layer of layer 2, and the outer fiber core of layer 3 are 41%:38%:21%, and the sum of the three is 100%.

[0042] This optical fiber has a 20 dB gain bandwidth of 183 nm, covering a wavelength range of approximately 1297–1480 nm. Its gain curve is broadened overall without significant dips. The thin transition layer and small k-value synergistically enhance the bandwidth, and the fabrication process is shorter, making it a preferred solution for ultra-wideband communication systems.

[0043] Example 4 This embodiment provides an ultrawideband bismuth-doped optical fiber with a gradient transition core layer, whose layered structure and doping active center type are the same as in Embodiment 1.

[0044] In this embodiment, the total core radius is 3.2 μm, the core radius of the inner layer of layer 1 is 1.75 μm, and the thickness of the gradient transition layer 2 is 1.2 μm. The refractive index distribution shape factor of the gradient transition layer 2 is k=2.8, and the refractive index difference between the refractive index n1 at the inner radius and the refractive index n2 at the outer radius is Δn1=0.008 and Δn2=0.006 (relative to pure quartz cladding). The concentration gradient index m=1, and the BAC-P concentration C1=4×10 16 cm - ³, BAC-Si concentration C3 = 10 × 10 16 cm - ³. The cross-sectional area ratio of the inner fiber core of layer 1, the gradient transition layer of layer 2, and the outer fiber core of layer 3 is 30%:55%:15%, wherein the cross-sectional area ratio of layer 2 reaches the upper limit of 55% of the preferred range of the present invention, which, together with the thick transition layer and the large k value, maximizes the mode field constraint capability.

[0045] This optical fiber has a 20 dB gain bandwidth of 166 nm, covering a wavelength range of approximately 1300–1466 nm. The large k-value and thick transition layer enhance mode field confinement, effectively reducing optical field leakage and making it suitable for long-distance, high-stability optical fiber transmission systems.

[0046] Example 5 This embodiment provides an ultrawideband bismuth-doped optical fiber with a gradient transition core layer, whose layered structure and doping active center type are the same as in Embodiment 1.

[0047] In this embodiment, the total core radius is 3.7 μm, the core radius of the inner layer of layer 1 is 1.85 μm, and the thickness of the gradient transition layer 2 is 1.0 μm. The refractive index distribution shape factor of the gradient transition layer 2 is k=2, and the refractive index difference between the refractive index n1 at the inner radius and the refractive index n2 at the outer radius is Δn1=0.008 and Δn2=0.006 (relative to pure quartz cladding). The concentration gradient index m=2, and the BAC-P concentration C1=3×10 16 cm - ³, BAC-Si concentration C3 = 11 × 10 16 cm - ³. The cross-sectional area ratios of the inner fiber core of layer 1, the gradient transition layer of layer 2, and the outer fiber core of layer 3 are 25%:41%:34%, and the sum of the three is 100%.

[0048] This optical fiber has a 20 dB gain bandwidth of 180 nm, covering a wavelength range of approximately 1320~1500 nm. The S-band gain is significantly increased, and the gain curve shifts towards longer wavelengths, making it suitable for dense wavelength division multiplexing transmission systems that focus on the S-band.

[0049] Example 6 This embodiment provides an ultrawideband bismuth-doped optical fiber with a gradient transition core layer, whose layered structure and doping active center type are the same as in Embodiment 1.

[0050] In this embodiment, the total core radius is 3.2 μm, the core radius of the inner layer of layer 1 is 1.75 μm, and the thickness of the gradient transition layer 2 is 1.0 μm. The refractive index distribution shape factor of the gradient transition layer 2 is k=2, and the refractive index difference between the refractive index n1 at the inner radius and the refractive index n2 at the outer radius is Δn1=0.008 and Δn2=0.006 (relative to pure quartz cladding). The concentration gradient index m=2, and the BAC-P concentration C1=4×10 16 cm - ³, BAC-Si concentration C3 = 12 × 10 16 cm - ³. The cross-sectional area ratios of the inner fiber core of layer 1, the gradient transition layer of layer 2, and the outer fiber core of layer 3 are 30%:44%:26%, and the sum of the three is 100%.

[0051] This optical fiber has a 20 dB gain bandwidth of approximately 183 nm, covering a wavelength range of approximately 1297~1480 nm. It can achieve stable amplification across the entire O+E+S band and is suitable for ultra-wideband optical fiber amplification systems.

[0052] Comparative Example This comparative example uses a traditional double-layer composite fiber core structure. The fiber consists of an inner core, an outer core, a low-refractive-index fluorine-doped quartz cladding, a pure quartz cladding, and an organic protective layer, from the inside out. A second, graded transition layer is omitted. The inner core is bismuth-phosphorus co-doped quartz glass containing phosphorus-associated bismuth active centers; the outer core is bismuth-germanium co-doped quartz glass containing silicon-associated bismuth active centers. A step-index interface exists between the two cores, with the inner core having a refractive index n1 = 1.4452 and the outer core having a refractive index n2 = 1.445. The inner core radius is 2.3 μm, and the outer core radius is 3.2 μm. The doping concentration is consistent with that of Example 6.

[0053] This structure has a 20 dB gain bandwidth of only 144 nm, which is significantly narrower than that of the embodiments of this invention. Furthermore, due to the lack of a gradient transition layer, there is a step abrupt change in refractive index, resulting in poor mode field continuity and weak mode stability. It is difficult to precisely control the refractive index interface using conventional fabrication processes, making it difficult to meet the application requirements of broadband fiber optic amplification systems.

[0054] Table 1 summarizes the key structural parameters of Examples 1-6 and the comparative examples and their corresponding ultrawideband amplification performance.

[0055] Table 1 As can be seen from Table 1, the optical fibers described in Examples 1-6 of this invention can all achieve continuous and smooth amplification across the entire O+E+S band, with a 20 dB gain bandwidth of no less than 166 nm, significantly higher than the 144 nm of the comparative example, and without any obvious gain dip. Among them, Examples 5 and 6, compared with the comparative example, respectively improve the gain of the E+S band and O+E band, and the 20 dB gain bandwidth of both is no less than 180 nm.

[0056] The results of the above embodiments demonstrate that the present invention achieves a dual gradient design of refractive index and doping concentration by setting a transition layer in the fiber core. This effectively solves the problems of insufficient synergy between the two active centers and gain dips at the band junctions in traditional layered doping schemes, significantly improving the spatial matching degree and optical field overlap efficiency of BAC-P and BAC-Si. Furthermore, by adjusting the thickness of the transition layer, the shape factor of the refractive index distribution, and the cross-sectional area ratio, different embodiments can flexibly optimize between gain bandwidth, mode stability, and gain intensity in specific bands, demonstrating significant application value in ultra-wideband fiber communication, dense wavelength division multiplexing systems, and optical amplification.

[0057] The ultrawideband composite bismuth-doped optical fiber with a graded transition core layer described in this invention can be prepared using a modified chemical vapor deposition (MCVD) method combined with solution doping. The specific steps are as follows: (1) A porous prefabricated layer consisting of an outer fiber core (layer 3), a gradient transition layer (layer 2), and an inner fiber core (layer 1) is sequentially deposited inside a quartz liner using the MCVD process. By precisely controlling the raw material ratio and deposition temperature during the deposition of each layer, the predetermined concentration distribution of phosphorus, germanium, and bismuth elements in the radial direction is achieved.

[0058] (2) For the gradient transition layer 2, the doping concentrations of Ge and P are continuously varied radially by adjusting the flow ratio of GeCl4 and POCl3 online, thereby achieving a power function gradient distribution of refractive index.

[0059] (3) The deposited porous preform is immersed in a doping solution containing bismuth ions for solution doping. By controlling the immersion time and solution concentration, combined with subsequent dehydration, sintering and vitrification processes, a predetermined concentration gradient distribution of bismuth ions is formed in each layer of the fiber core.

[0060] (4) The vitrified preform is shrunk into a solid preform at high temperature, and then subjected to stretching, cladding deposition, secondary drawing and other processes to finally obtain an optical fiber with a target core diameter (6.4-8.4 μm) and cladding diameter (125 μm).

[0061] It should be understood that the above preparation method is only an illustrative example. Those skilled in the art can also use other mature optical fiber preparation processes (such as rare earth rod stacking method, external vapor deposition method, etc.) to realize the optical fiber structure described in this invention, and these are all within the protection scope of this invention.

[0062] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the embodiments described. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A bismuth-doped composite fiber with a graded transition core layer for ultrawideband amplification, characterized in that, The optical fiber comprises, from the inside out, a fiber core, a low-refractive-index fluorine-doped quartz cladding, a pure quartz cladding, and an organic protective layer; wherein, the fiber core adopts a coaxial three-layer structure, which consists of, from the inside out, an inner fiber core layer 1, a graded transition layer layer 2, and an outer fiber core layer 3. The inner core of layer 1 is bismuth-phosphorus co-doped quartz glass containing phosphorus-associated bismuth active centers BAC-P; The outer core of layer 3 is bismuth-germanium co-doped quartz glass containing silicon-associated bismuth active centers BAC-Si; The gradient transition layer 2 is a bismuth-phosphorus-germanium co-doped quartz glass, containing both BAC-P and BAC-Si. The refractive index of the gradient transition layer 2 decreases continuously from the inside to the outside in the radial direction; in the gradient transition layer 2, the concentration of BAC-P decreases continuously and monotonically from the inside to the outside in the radial direction, and the concentration of BAC-Si increases continuously and monotonically from the inside to the outside in the radial direction. The optical fiber has single-mode amplification characteristics in the O+E+S band.

2. The ultra-wideband amplification composite bismuth-doped optical fiber with a graded transition core layer according to claim 1, characterized in that, The fiber core diameter is 6.4–8.4 μm, the cladding diameter is 125 μm, and the core radius r3 ranges from 3.2 to 4.2 μm. Within the radial interval [r1, r2], the radial thickness d = r2 - r1 of the graded transition layer 2 is 0.8–1.2 μm, where r1 is the radius of the inner core of layer 1 (which is also the inner radius of the graded transition layer 2), and r2 is the outer radius of the graded transition layer 2, satisfying 0. <r1<r2<r3。 3. The ultra-wideband amplification composite bismuth-doped optical fiber with a graded transition core layer according to claim 2, characterized in that, Within the radial interval [r1, r2], the refractive index decreases radially from the inside out in a power function manner, and the refractive index at any point... satisfy In the formula, r1 is the radius of the inner core of layer 1, with a value range of 1.75≤r1≤2.05; r2 is the outer radius of the gradient transition layer of layer 2, satisfying r2=r1+d, 0.8≤d≤1.2; n1 is the refractive index at r=r1, n2 is the refractive index at r=r2, and satisfies 1.452>n1>n2>1.444 (relative to the refractive index n of pure quartz cladding). SiO2 =1.444). k The refractive index distribution shape factor has a value range of 1.5 ≤ k ≤2.

8.

4. The ultrawideband composite bismuth-doped optical fiber with a graded transition core layer according to claim 1, characterized in that, Within the radial range [r1, r2] of the gradient transition layer 2, the concentration of phosphorus-associated bismuth active centers (BAC-P) decreases continuously from the inside to the outside in a power-law manner, while the concentration of silicon-associated bismuth active centers (BAC-Si) increases continuously from the inside to the outside in a power-law manner. The concentration of BAC-P... C BAC-P and the concentration of BAC-Si C BAC-Si They respectively satisfy: in, m Let be the gradient exponent, and 1 ≤ m ≤3; C 1 represents the BAC-P concentration at radial position r1 of the inner fiber core of layer 1. C 3 represents the BAC-Si concentration at radial position r2 of the outer fiber core of layer 3; and C 1≥3×10 16 cm 3 , C 3≥9×10 16 cm 3 .

5. The ultra-wideband composite bismuth-doped optical fiber with a graded transition core layer according to claim 1, characterized in that, The cross-sectional areas of the inner fiber core of layer 1, the gradient transition layer of layer 2, and the outer fiber core of layer 3 account for 22%~41%, 28%~55%, and 15%~50% of the total cross-sectional area of ​​the fiber core, respectively, and the sum of the three is 100%.

6. The ultra-wideband composite bismuth-doped optical fiber with a graded transition core layer according to claim 1, characterized in that, The pure quartz cladding is SiO2 glass; the organic protective layer is polyimide or UV-cured acrylate.

7. An ultra-wideband fiber optic amplification system, characterized in that, The system comprises an ultrawideband composite bismuth-doped optical fiber with a gradient transition core layer as described in any one of claims 1 to 6.

8. A method for preparing an ultrawideband composite bismuth-doped optical fiber with a graded transition core layer, characterized in that, The method includes the following steps: The optical fibers according to any one of claims 1 to 6 are prepared by an improved chemical vapor deposition method combined with solution doping. By adjusting the flow ratio of GeCl4 and POCl3 during the deposition process, the refractive index of the gradient transition layer 2 is made to exhibit a power-law continuous gradient distribution along the radial direction. By controlling the soaking time and solution concentration of the solution doping, the concentrations of BAC-P and BAC-Si in the gradient transition layer of layer 2 are made to show a continuous monotonically decreasing and a continuous monotonically increasing distribution along the radial direction, respectively.

9. The preparation method according to claim 8, characterized in that, The method further includes the following steps: sequentially depositing a porous preform layer of the outer core of layer 3, the gradient transition layer of layer 2, and the inner core of layer 1 inside a quartz liner; immersing the deposited porous preform in a bismuth-containing doping solution for solution doping; forming a preform through dehydration, sintering, and vitrification processes, and then obtaining the optical fiber through rod shrinking, stretching, cladding deposition, and secondary drawing.

Citation Information

Patent Citations

  • Laser fiber with gradually changed radial doping concentration and preparation method thereof

    CN113359229A